DAMAGE ASSESSMENT AND DIAGNOSIS – Alhos-Vedros tide-mill, Moita - Gonçalves, T. D. (2014)
This report concerns Alhos-Vedros tide-mill, Moita, which was used as a case-study of the EU project COMPASS. It focuses the assessment of damage, diagnosis and advice for repair of salt decay anomalies. It concludes that, in the ground floor, plaster damage is due to the simultaneous presence of moisture and salts. Capillary rise and leakage from the cover roof and window frames are two obvious origins of moisture. Water vapour condensation is also a possible source of moisture but the knowledge of its relevance requires further testing.